Effect of crushed limestone sand and dust on the mechanical behaviour of river sand mixtures: an experimental study - Benyahia, Ahmed Bilal; Irki, Ilyes; Djafar Henni, Ahmed; Ezziane, Mohammed; Laidani, Zine el abidine (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction: The present study aims to investigate the effect of crushed limestone sand (CLS) and limestone crushed sand dust (LCSD) on the physical and mechanical behaviour of reconstituted river sand (RS) using the volumetric substitution method. Methods: The study involved conducting direct shear tests on two substitution series to evaluate the effect of CLS sand with incremental increases of 0, 10, 20, 30, and 40%, and LCSD dust ranging from 0 to 35% in 5% steps on the mechanical behaviour of reconstituted river sand. All samples are prepared with 50% relative density and tested under three different normal stresses of 100, 200, and 300 kPa, respectively. Results: The results show that the substitution of river sand with CLS up to 30% enhances its mechanical properties; the peak shear strength reached a maximum value of 29% under 200 kPa of normal stress. The substitution of river sand for LSCD leads to a decrease in mechanical properties. However, a more in-depth analysis of the results obtained reveals an improvement in residual parameters, with up to 15% of substitution. Conclusion: Following a rigorous analysis of the obtained results, it was determined that sand reconstituted from a combination of 30% CLS and 15% LCSD offers optimal performance in terms of enhanced mechanical properties. This solution aligns significantly with the sustainable development of the Algerian government strategy promoting improved characteristics and preserving natural resources while meeting the stringent requirements of the geotechnical sector.